The influence of managerial competence and achievement motivation on the leadership effectiveness of high school principals - Daulay, Basyaruddin; Haidir, Haidir; Firmansyah, Firmansyah (Jurnal Cakrawala Pendidikan, 2024)
This study investigates the impact of managerial competence and achievement motivation on the leadership effectiveness of high school principals in Medan City. Employing a robust quantitative approach, the research encompasses a total population of 231 principals, from which a representative of 144 individuals was drawn utilizing the Cochran formula for sample. Questionnaires with a Likert scale were used for data collection. The analytic framework involves path analysis to elucidate the relationships between variables. Empirical findings from the path analysis underscore the significant direct effects of managerial competence and achievement motivation on leadership effectiveness, with path coefficients of  0.164 and 0.189, respectively. The results highlight the critical role of enhancing managerial skills and fostering motivational drives among principals to elevate their leadership capabilities. Consequently, the study advocates for strategic initiatives to bolster these competencies to advance leadership effectiveness in the educational sector.